Electrochemical Determination of Mycophenolate Mofetil in Drug Samples Using Carbon Paste Electrode Modified with 1-methyl-3-butylimidazolium Bromide and NiO/SWCNTs Nanocomposite - Hosseini, Firuzeh; Ebrahimi, Mahmoud; Karimi-Maleh, Hassan (Current Analytical Chemistry, 2019)
Background: The mycophenolate mofetil is an immunosuppressant drug with wide application in the treatment of cancer and prevent rejection in organ transplantation. This drug showed many sides effects for pregnant women and determination of this drug is very important in the human body. Objective: A new electrochemical strategy was described for analysis of Mycophenolate Mofetil (MMF) using novel voltammetric sensor. The sensor was fabricated using NiO/SWCNTs and 1-methyl- 3-butylimidazolium bromide as two conductive mediators for modification of carbon paste electrode (NiO/SWCNTs/MBBr/CPE). The NiO/SWCNTs/MBBr/CPE can be used for analysis of MMF in aqueous buffer solution in the concentration range of 0.08-900 μM. In addition, the NiO/SWCNTs/ MBBr/CPE reduced oxidation over-potential of MMF 80 mV and increased the oxidation current of MMF 2.85 times. In the final step, NiO/SWCNTs/MBBr/CPE was used for determination of MMF in pharmaceutical serum and tablet samples.
Keywords: 1-methyl-3-butylimidazolium bromide